2021
DOI: 10.1590/0100-6991e-20202633
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol (70%) versus alcoholic chlorhexidine solution (0.5%) in skin antisepsis for neuraxial blocks: a randomized clinical trial

Abstract: Objective: to compare the use of 0.5% alcoholic chlorhexidine and 70% alcohol in skin antisepsis for neuraxial blocks. Method: this is a non-inferiority randomized clinical trial, with two parallel arms. Seventy patients who were candidates for neuraxial block were randomly allocated to group A (n = 35), in whom antisepsis was performed with 0.5% alcoholic chlorhexidine, or to group B (n = 35), in whom we used 70% hydrated ethyl alcohol. Swabs were harvested for culture at three times: before antisepsis, tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…In a study comparing 0.5% alcoholic chlorhexidine with 70% hydrated ethyl alcohol for skin antisepsis for neuraxial blocks, it was shown that 70% alcohol was more effective in reducing the number of colony forming units (CFU/cm²) after two minutes, and there was no difference between the two groups in terms of skin colonization at the end of the procedure. 14 To verify whether two applications of chlorhexidine/ethanol solution are more effective than one for skin disinfection before neuraxial anesthesia, the result showed that the application of chlorhexidine/ethanol once is sufficient to disinfect the skin for regional anesthesia, and that the 2 nd application may be delayed in an emergency situation, and this 2 nd application increases the risk of translocation of chlorhexidine to the subarachnoid space. 15…”
Section: Introductionmentioning
confidence: 99%
“…In a study comparing 0.5% alcoholic chlorhexidine with 70% hydrated ethyl alcohol for skin antisepsis for neuraxial blocks, it was shown that 70% alcohol was more effective in reducing the number of colony forming units (CFU/cm²) after two minutes, and there was no difference between the two groups in terms of skin colonization at the end of the procedure. 14 To verify whether two applications of chlorhexidine/ethanol solution are more effective than one for skin disinfection before neuraxial anesthesia, the result showed that the application of chlorhexidine/ethanol once is sufficient to disinfect the skin for regional anesthesia, and that the 2 nd application may be delayed in an emergency situation, and this 2 nd application increases the risk of translocation of chlorhexidine to the subarachnoid space. 15…”
Section: Introductionmentioning
confidence: 99%
“…In a study comparing 0.5% alcoholic chlorhexidine with 70% hydrated ethyl alcohol for skin antisepsis for neuraxial blocks, it was shown that 70% alcohol was more effective in reducing the number of colony forming units (CFU/cm²) after two minutes, and there was no difference between the two groups in terms of skin colonization at the end of the procedure. 14 To verify whether two applications of chlorhexidine/ethanol solution are more effective than one for skin disinfection before neuraxial anesthesia, the result showed that the application of chlorhexidine/ethanol once is sufficient to disinfect the skin for regional anesthesia, and that the 2 nd application may be delayed in an emergency situation, and this 2 nd application increases the risk of translocation of chlorhexidine to the subarachnoid space. 15…”
Section: Introductionmentioning
confidence: 99%